Eficácia da utilização da solução custodiol versus a solução celsior como métodos de preservação do enxerto no transplante cardíaco - Fernandes, Marcio Pimentel (Universidade Federal de São Carlos, 2020)
Heart transplantation may be the only treatment opportunity for those individuals with end-stage heart disease. Heart preservation is currently limited to 4 hours in cold ischemia storage using preservation solutions, and is an indispensable factor for graft function and survival in transplantation. The mortality rate is mainly related to graft failure in transplantation, so that techniques capable of improving graft function can directly influence the patient's survival. Objective: To analyze in the scientific literature the efficacy between custodyol versus celsior solution as the best method of graft preservation in heart transplantation. Method: This is an integrative review of the literature, directed according to the structure of PICOS, followed by research in the electronic databases: Pubmed, Virtual Health Library and Embase, to research the articles. As keywords we use heart transplantation and its synonyms, Celsior, and Cutodiol and its synonyms. Results: In all, 22 studies were analyzed, of which only 4 were included in the review, one clinical trial, one meta-analysis and two retrospective studies. Mortality and myocardial dysfunction after heart transplants were investigated. Conclusion: After the analysis of the articles under study, it was not possible to identify between the two solutions Celsior and Custdiol a superiority of one over the other in post-transplant mortality and graft dysfunction after transplantation.
Efficacy of using the custodiol solution versus the celsior solution as methods of graft preservation in heart transplantation
Keywords: Transplante cardíaco; Celsior; Custodiol; Heart transplantation; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::MEDICINA; CIENCIAS DA SAUDE